De urinis et pulsibus de Gilles de Corbeil y De urinis de Pierleone da Spoleto, un raro de 1514 conservado en la Biblioteca de la Universidad de La Laguna - Martínez Benavides, María José; Fernández Palomeque, Paz; González Marrero, José Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
The medical practice and experimentation undertaken in the Salerno School represent a point of contact between Greek medicine, monastic medicine and Arabian medicine. The innovation of printing lead to the preservation of ancient traditions and of religious commentaries which were systematized and brought